Pendampingan Praktikum Defleksi Elektron untuk Siswa Sekolah Menengah Atas di Surabaya - Herwinarso Herwinarso; Anthony Wijaya; Jane Koswojo; Tri Lestari; Bergitta Dwi Annawati; Yeremia Kristiawan; Elisabeth Pratidhina (Jurnal Pengabdian Masyarakat Waradin, 2025)
Physics learning in high schools is often facing challenges due to lack of laboratory facilities, especially for abstract topics such as electron deflection. Limited equipment often results in a theoretical learning process without real-world practical experience. This community service activity aims to address this gap by assisting with electron deflection experiments at a high school in Surabaya. The methods applied included preparation and coordination, provision of equipment, inquiry-based learning design, classroom experiment implementation, and activity evaluation. During the program, the team brought the electron deflection experiment equipment to the school. Students were divided into small groups, and each group took turns interacting closely with the equipment brought by the team. Students were encouraged to propose hypotheses, observe carefully, and engage in discussions. A total of 58 students participated in this activity and had the opportunity to directly observe electron path in a cathode ray tube. The evaluation showed an excellent response from students with an average score of 3.48 (scale 1–4), where they felt this activity helped them learn theory with practice and increased their enthusiasm for learning. This program demonstrates that collaboration between universities and schools can be an efficient solution to overcome the lack of laboratory facilities and improve the quality of more meaningful physics learning.